Scarcity of Specific Resources as a Limit to Output - Guha, Ashok (Review of Economic Studies, 1963)
Journal Article Scarcity of Specific Resources as a Limit to Output Get access Ashok Guha Ashok Guha Cambridge, Mass. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 30, Issue 1, February 1963, Pages 37–42, https://doi.org/10.2307/2296029 Published: 01 February 1963